Utilization of Potassium Carbonate-Ethylene Glycol as Deep Eutectic Solvent to Delignification Oil Palm Empty Fruit Bunch for Furfural and Ethanol Production - Muryanto; Amelia, Fanny; Nurbayti, Siti; Sudiyani, Yanni; Gozan, Misri (BRIN Publishing (Penerbit BRIN), 2024)
Pretreatment using Deep Eutectic Solvent (DES) was done to reduce the lignin content in oil palm empty fruit bunch (OPEFB). DES solution was prepared by combining Potassium Carbonate (K2CO3) as hydrogen bond acceptors (HBA) and Ethylene Glycol (EG) as hydrogen bond donors (HBD). This study aimed to obtain optimum conditions in the pretreatment process and determine the levels of lignin, cellulose, hemicellulose, and glucose in OPEFB. The pretreatment stage was performed at different temperature parameters, 100, 120, and 150°C, for 60 minutes to produce optimum conditions. Biomass pretreated with DES was hydrolyzed by cellulase complex to obtain glycose and xylose. The results showed that the pretreatment optimum condition value achieved with DES K2CO3:EG (1:10) at 150°C for 60 minutes was able to degrade lignin by 46,06%, hemicellulose by 4,08%, increase cellulose by 60,21%. The glucose and xylose content reached 58.48 g/l and 26.60 g/l, respectively. This sugar has potential for ethanol production from glucose and furfural production from xylose.